1997
DOI: 10.1046/j.1365-2222.1997.d01-489.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of murine cutaneous late phase reaction requires both IgE antibodies and CD4 T cells

Abstract: It is suggested that murine cutaneous LPR against OVA is a type 2 inflammatory response in which both IgE antibodies and CD4 T cells play an obligatory role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Our experiments using mast cell-deficient W/W v mice suggest that the biphasic cutaneous reactions are dependent on activation of mast cells, and it has been shown that antigen-specific IgE 20 and FceRI 24 are essential for development of the biphasic reactions as seen in this model, which indicates that findings in the W/W v mouse are relevant to the human IHR. Depletion of about 90% of circulating platelets in the mice significantly reduced the LPR, suggesting that platelets are important for leukocyte recruitment into skin.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our experiments using mast cell-deficient W/W v mice suggest that the biphasic cutaneous reactions are dependent on activation of mast cells, and it has been shown that antigen-specific IgE 20 and FceRI 24 are essential for development of the biphasic reactions as seen in this model, which indicates that findings in the W/W v mouse are relevant to the human IHR. Depletion of about 90% of circulating platelets in the mice significantly reduced the LPR, suggesting that platelets are important for leukocyte recruitment into skin.…”
Section: Discussionmentioning
confidence: 78%
“…20 Mice were sensitized by intraperitoneal injection of 3 mg ovalbumin (Sigma-Aldrich, St Louis, Mo) and 4 mg aluminum hydroxide gel. Reactions to ovalbumin were elicited by intracutaneous injection of 10 mg ovalbumin into the right ear of mice 2 weeks after sensitization, with an identical amount of vehicle injected into the left ear as a control.…”
Section: Immunizationmentioning
confidence: 99%
“…As described previously (Sawada et al, 1997;Cho et al, 2001;Pavlovic et al, 2008), mice were sensitized to ovalbumin (20 mg, grade VI, Sigma-Aldrich Chemie, Schnelldorf, Germany) on days 7 and 28 of the experimental protocol. AlD was induced by intradermal injection of ovalbumin (50 mg, grade V, Sigma-Aldrich Chemie) on day 35.…”
Section: The Ald-stress Modelmentioning
confidence: 99%
“…These cytokines have been reported to be involved in eosinophil recruitment, suggesting that either CD4 T cells, mast cells, or both play a role in development of the antigen-induced LTR. The OVAinduced biphasic cutaneous reaction is well documented to show both the ITR and the LTR (33,34).…”
Section: Discussionmentioning
confidence: 99%